A Visible Light Photocatalyst of Carbonate‐Like Species Doped TiO2. Issue 1 (6th October 2016) - Yu, Linhui; Lin, Yangming; Huang, Jing; Lin, Sen; Li, Danzhen
Abstract : Carbon‐doped TiO2 nanomaterials have been successfully synthesized via an effective two‐step procedure involving hydrothermal method and followed by a low‐temperature calcination treatment process, through which a controllable amount of carbonate‐like species could be incorporated into TiO2 . First‐principles calculations suggest the TiO2 doped with carbon in form of carbonate‐like species can effectively extend the adsorption of the material from ultraviolet region to visible light. And it is experimentally found that carbon‐doped TiO2 nanomaterials exhibit much higher photocatalytic activity than reference P25 and TiO2− x N x catalysts toward the liquid‐phase degradation of organic pollutants under visible light (420 nm < λ < 800 nm) irradiation. The presence of synergic effect between carbonate‐like doping and anatase TiO2 is believed to play an essential role in affecting the photocatalytic reactivity, and the response to the visible light is ascribed to the narrowed band gap energy controlled by carbon doping. Moreover, the roles of active species in the photocatalytic process are compared using different types of active species scavengers. Meanwhile, the degradation mechanism of the photocatalysis is proposed. It is hoped that our work could provide valuable information on the design of carbonate‐like doped semiconductor with more excellent properties and set the foundation for the further industrial application.